Waqf Law in the Muslim World: A Study of the Organization and Administration of Waqf in Tunisia - Cipto Sembodo; Zainul Arifin; Ahmad Syafii Rahman; Supriati Hardi Rahayu (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2025)
This research examines Islamic waqf in Tunisia, a topic that is rarely discussed in contemporary studies, especially from a historical and sociological perspective. Most of the existing studies focus more on normative aspects such as the laws, conditions, and pillars of waqf. In contrast, empirical research looking at the historical and sociological aspects of Islamic waqf is limited to local cases. Tunisia, which is known to be liberal in Islamic law reform, especially in the field of family law, rarely has in-depth studies on waqf. The purpose of this study is to analyse the organisation and administration of waqf in Tunisia and its impact on society. The research uses the literature method with a normative juridical approach which is descriptive analytical in nature. The results show that the organisation and administration of waqf in Tunisia are influenced by internal Muslim factors as well as government policies. The government, in particular, has a very dominant influence in the process. There are two main motivations from the ruling party: first, economic motivation that emerged since the French protectorate, which encouraged economic capitalisation; second, political motivation that initially supported certain political processes, but later developed for other political interests, as happened during the time of President Habib Bourguiba. The practice of waqf administration in Tunisia mostly involves administrative reform efforts in the broader context of Islamic law. Although there is no clear form of productive waqf, waqf in Tunisia has evolved in terms of its form and implementation mechanism in a more professional manner.